FEATURES OF DIALECTAL WORDS THAT FILL IN THE GAPS IN THE LANGUAGE VOCABULARY - Khasanov Abdumannon Majidovich (International Journal on Integrated Education, 2021)
This article is devoted to filling the lexical gaps in the Uzbek language with of folk dialects. The proverb shows the norms and criteria for enriching lexical lacunaein modern Uzbek with dialectal word. The mechanisms of application of these criteria are explained by examples. The article pays special attention to the issue of enriching the gaps in the lexicon of literary language with dialectical words. Therefore, comments were made on the lexical spatial properties of the selected dialectical words. For example, it explains how dialectical words that correspond to a lexical lacuna meet language requirements. The possibilities of literalization of these words and thenegative and positive factors influencing them are also analyzed. The aspects of these factors that prevent dialectical words from becoming a literary linguistic unit are also described.